Hydraulic-Hydrology Analysis of the Turbulent Seepage Flow within Karst Aquifer of the Golubinka Spring Catchment - Goran Lončar; Željko Šreng; Damir Bekić; Duška Kunštek (Geofluids)
This paper shows the results of the hydraulic-hydrologic calculations of karst spring discharges and the groundwater level in the aquifer of spring catchment. The calculations were performed for the Golubinka spring in Zadar area for the 4-year period. The chosen approach was a model using relatively scarce data set, including limnigraphic data on the difference between the sea water level and the freshwater level on the spring itself and the precipitation data from the meteorological station Zadar. The determination of discharge hydrographs, based on inherent assumptions and available data, yields the proportionality coefficients between the discharge and the limnigraphic data on the Golubinka spring itself. Further, based on the discharge hydrograph, groundwater level oscillation was determined. The resulting spring discharge hydrograph and groundwater levels, along with the assumption of Golubinka spring as the only spring on the catchment, were used in creating turbulent seepage model of the fractured system within the aquifer, which evidently extends along the axis of the Golubinka spring catchment. The model yielded suitable turbulent seepage coefficients of the fracture system. By using the numerical model KarstMod it was estimated that, on average, concentrated fracture flow drains around 85% of infiltrated volumes and the remaining 15% accounts for diffuse matrix flow. Finally, the Modflow model was used in order to get insight into the flow field and the distribution of equipotentials in the aquifer of the Golubinka catchment.